2021
DOI: 10.1007/s12079-021-00624-4
|View full text |Cite
|
Sign up to set email alerts
|

Activated fibroblasts enhance cancer cell migration by microvesicles-mediated transfer of Galectin-1

Abstract: Cancer-associated fibroblasts (CAFs) are one of the main components of the stromal compartment in the tumor microenvironment (TME) and the crosstalk between CAFs and cancer cells is essential for tumor progression and aggressiveness. Cancer cells mediate an activation process, converting normal fibroblasts into CAFs, that are characterized by modified expression of many proteins and increased production and release of microvesicles (MVs), extracellular vesicles generated by outwards budding from the cell membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…Another study showed that PDGF induced a migration response at concentrations of 1–5 ng/mL, while at higher concentrations (>5 ng/mL), PDGF induced proliferation but not migration of NIH3T3 fibroblasts [ 56 ]. Additionally, Toti et al showed that microvesicles-mediated transfer of Galectin-1 proteins from fibroblasts stimulates cell migration [ 57 ]. These studies suggest that the concentration of cytokines as well as specific proteins in the secretome from myoblasts lead to different outcomes on cell migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that PDGF induced a migration response at concentrations of 1–5 ng/mL, while at higher concentrations (>5 ng/mL), PDGF induced proliferation but not migration of NIH3T3 fibroblasts [ 56 ]. Additionally, Toti et al showed that microvesicles-mediated transfer of Galectin-1 proteins from fibroblasts stimulates cell migration [ 57 ]. These studies suggest that the concentration of cytokines as well as specific proteins in the secretome from myoblasts lead to different outcomes on cell migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a proteomic analysis of human breast cancer tissues revealed that galectin-1 is upregulated in cancer-associated stroma tissue. And natriuretic peptide B (NPPB), increasing in ovarian cancer stroma compared with normal ovarian stroma, also has been identified as a potential candidate marker for CAFs [16,17].…”
Section: Function and Heterogeneity Of Cafsmentioning
confidence: 99%
“…The interactions in the tumor microenvironment are considered another critical mechanism for cancer progression that assimilate peripheral cells through secretion of various molecules [ 133 , 134 ]. Furthermore, there are various cells surrounding the microenvironment, such as stromal cells and immune cells, which are reportedly regulated by Gals [ 82 , 135 , 136 ]. Additionally, immune evasion is one of the most important mechanisms for cancer survival [ 137 ].…”
Section: Galectin In the Microenvironmentmentioning
confidence: 99%
“…In contrast, Higareda-Almaraz and coworkers showed that Gal-7 is a negative regulator of cervical cancer that acts through reprogramming the tumor microenvironment [ 78 ]. Interestingly, fibroblasts were shown to be activated by cancer cells known as cancer-associated fibroblasts, and the expression of Gals was associated with fibroblast activation and promoted growth [ 135 , 136 ]. Toti et al found that knockdown of Gal-1 in tumor stromal cells, such as human pancreatic stellate cells, decreased pancreatic ductal adenocarcinoma growth in vivo [ 97 ].…”
Section: Galectin In the Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation